Novel Lipidated Imidazoquinoline TLR7/8 Adjuvants Elicit Influenza-Specific Th1 Immune Responses and Protect Against Heterologous H3N2 Influenza Challenge in Mice - Miller, Shannon M.; Cybulski, Van; Whitacre, Margaret; Bess, Laura S.; Livesay, Mark T.; Walsh, Lois; Burkhart, David; Bazin, Hélène G.; Evans, Jay T. (Frontiers in Immunology, 2020)
Most licensed seasonal influenza vaccines are non-adjuvanted and rely primarily on vaccine-induced antibody titers for protection. As such, seasonal antigenic drift and suboptimal vaccine strain selection often results in reduced vaccine efficacy. Further, seasonal H3N2 influenza vaccines demonstrate poor efficacy compared to H1N1 and influenza type B vaccines. New vaccines, adjuvants, or delivery technologies that can induce broader or cross-seasonal protection against drifted influenza virus strains, likely through induction of protective T cell responses, are urgently needed. Here, we report novel lipidated TLR7/8 ligands that act as strong adjuvants to promote influenza-virus specific Th1-and Th17-polarized T cell responses and humoral responses in mice with no observable toxicity. Further, the adjuvanted influenza vaccine provided protection against a heterologous H3N2 influenza challenge in mice. These responses were further enhanced when combined with a synthetic TLR4 ligand adjuvant. Despite differences between human and mouse TLR7/8, these novel lipidated imidazoquinolines induced the production of cytokines required to polarize a Th1 and Th17 immune response in human PBMCs providing additional support for further development of these compounds as novel adjuvants for the induction of broad supra-seasonal protection from influenza virus.